Hope in a jar: the making of America's beauty culture - Peiss, Kathy Lee (Henry Holt, 1999)
How did powder and paint, once scorned as immoral, become indispensable to millions of respectable women? How did a Victorian "kitchen physic," as homemade cosmetics were called, become a multi-billion-dollar industry? In Hope in a Jar, historian Kathy Peiss gives us a vivid history in which women, far from being pawns and victims, used makeup to declare their freedom, identity, and sexual allure as they flocked to enter public life. She highlights the leading role of black and white women-Helena Rubenstein and Annie Turnbo Malone, Elizabeth Arden and Madame C.J. Walker-in shaping a unique industry that relied less on advertising than on women's customs of visiting ("Avon calling") and conversation. From New York's genteel enameling studios to Memphis's straightening parlors, Peiss depicts the beauty trades that thrived until the 1920s, when corporations run by men entered the lucrative field, creating a mass consumer culture that codified modern femininity. Replete with the voices and experiences of ordinary women, Hope in a Jar is a richly textured account of how women created the cosmetics industry and cosmetics created the modern woman.
Keywords: Business History and gender